The natural history of multiple sclerosis: a geographically based study. 7. Progressive-relapsing and relapsing-progressive multiple sclerosis: a re-evaluation. - Kremenchutzky, M; Cottrell, D; Rice, G; Hader, W; Baskerville, J; Koopman, W; Ebers, G (1999)
Classifications of multiple sclerosis subtypes have been largely based on clinical phenomenology. Nevertheless, definitions of relapse, remission and progression have been imprecise. Recently an international consensus group, as part of a reclassification of disease subtypes, recommended dropping the term 'relapsing-progressive' (RP) and retaining the term 'progressive-relapsing' (PR) multiple sclerosis. The term 'RP' multiple sclerosis had been applied when the early course combined both relapses and progression and was believed to identify some patients with a worse than average outcome. The PR group consisted of patients with primary progressive disease who later in their course developed relapses. Since the terminology has been largely arbitrary, we have evaluated the validity of the terms 'RP' and 'PR' multiple sclerosis in the context of long-term outcome within a large population-based cohort of progressive multiple sclerosis patients seen at the London Multiple Sclerosis Clinic (Canada) between 1972 and 1984. Mean follow-up of the entire cohort was 25 years. Designation of RP multiple sclerosis did identify a more rapidly progressive subgroup. To realign these natural history data with consensus recommendations, these patients were reassigned to secondary progressive (SP) or to primary progressive (PP) multiple sclerosis, with progression defined as at least 1 year of progressive deterioration. PP multiple sclerosis patients with relapses after a year were designated as having PR multiple sclerosis. Relapses in primary progressive multiple sclerosis occurred in 27.8% of patients at some point even two to three decades after onset. In general these relapses were mild and remitting, but served to blur the distinction between progressive and relapsing-remitting disease. The long-term outcomes of time to Kurtzke disability scores (DSS) of 3, 6, 8 and 10 were compared among the progressive subtypes. Times to these disability end-points and to death were not different between PR and PP multiple sclerosis. Survival curves for progressive patients have been amended to incorporate the reassignment of PR multiple sclerosis patients into the PP group and the RP multiple sclerosis patients into the PP and SP subgroups. The time to reach DDS 3, 6, 8 and 10 for a population-based cohort of primary and secondary progressive patients resulting from the elimination of the categories of RP multiple sclerosis and PR multiple sclerosis has been established. These results provide justification for retaining only PP and SP multiple sclerosis as the subgroups of progressive disease.